El Derecho en Mesopotamia - Ibarra-Torres , Elba (Vida Científica Boletín Científico de la Escuela Preparatoria No. 4, 2020)
In any social life, customs, traditions and laws are necessary elements for the good development and stability of the same from the antiquity. Law, as a socio-cultural part, is fundamental within evolutionary relationships in different peoples and nations, as a result of an evolutionary process where great civilizations have participated in the Development of humanity. It is important that today we know the changes, the diversity of factors and the legacy that some civilizations have left over time. This is the case of one of one of the great first civilizations known as Mesopotamia that by Greek name means “Place between rivers” there in that region the Sumerians develop which was a civilization that proved to be one of the first civilizations to have a viable System of government. Analysing all the socio-cultural dimensions of the emergence of ancient law requires a deep analysis, however in this work I intend to illustrate how since ancient times societies have needed rules and / or laws for a healthy human life